Protection of Minors in the Legislation of the Diocese of Tarnów - Robert Kantor (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The sexual abuse of a child is a crime which demands a response on various levels. On the one hand, it requires psychological support for the victims, while on the other, it requires concrete legal and penal measures against the perpetrators, as well as broad social education and preventive measures in order to prevent similar tragedies from recurring in the future. The document entitled “Protection of Minors in the Pastoral Work of the Diocese of Tarnów – Norms and Rules” refers to the actions of the universal Church. The document on the protection of minors is a guideline for the Diocese of Tarnów to be used in all parishes, communities and works of the diocese, both by clergymen, consecrated persons and laity who undertake ministry among children and young people.